2020-2021 field seasons of Maize GxE project within the Genomes to Fields Initiative - Dayane Cristina Lima; Alejandro Castro Aviles; Ryan Timothy Alpers; Alden Perkins; Dylan L Schoemaker; Martin Costa; Kathryn J. Michel; Shawn Kaeppler; David Ertl; Maria Cinta Romay; Joseph L. Gage; James Holland; et al. (BMC Research Notes, 2023)
Abstract Objectives This release note describes the Maize GxE project datasets within the Genomes to Fields (G2F) Initiative. The Maize GxE project aims to understand genotype by environment (GxE) interactions and use the information collected to improve resource allocation efficiency and increase genotype predictability and stability, particularly in scenarios of variable environmental patterns. Hybrids and inbreds are evaluated across multiple environments and phenotypic, genotypic, environmental, and metadata information are made publicly available. Data description The datasets include phenotypic data of the hybrids and inbreds evaluated in 30 locations across the US and one location in Germany in 2020 and 2021, soil and climatic measurements and metadata information for all environments (combination of year and location), ReadMe, and description files for each data type. A set of common hybrids is present in each environment to connect with previous evaluations. Each environment had a collaborator responsible for collecting and submitting the data, the GxE coordination team combined all the collected information and removed obvious erroneous data. Collaborators received the combined data to use, verify and declare that the data generated in their own environments was accurate. Combined data is released to the public with minimal filtering to maintain fidelity to the original data.